Comparative Evaluation of Clear Twin Block and Conventional Twin Block in the Correction of Skeletal Class II Malocclusion: A Systematic Review and Meta-Analysis - Shubhangi Amit Mani; Vinaya Kumar Kulkarni; Dhananjay Gandage; Vikranth Omprakash Shetty; Sourabh Ramesh Joshi; Vandana Tripathi (Journal of International Clinical Dental Research Organization)
Introduction: The term “malocclusion” describes the misalignment that occurs during jaw closure in both dynamic and static stages due to the inappropriate contact of the maxillary and mandibular teeth. Class II malocclusion comprises of 16% of the total malocclusions. Functional appliances, such as twin blocks (TBs), are designed to correct these by stimulating neuromuscular reflexes and aligning the developing jaws during the pubertal growth spurt. TB in comparison with clear TB (CTB) has disadvantage of being a bulky appliance and limited patient acceptance. Conflicting results have been found while comparing CTB with conventional TB; hence, a systematic review with meta-analysis was designed. Methods: A systematic review of literature and meta-analysis was performed to know if there is any difference between CTB and conventional TB appliances in the correction of skeletal Class II malocclusion. The study followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and it was registered under PROSPERO. Studies were selected using Population, Intervention, Comparison, Outcomes, and Study (PICOS) criteria and electronic data resources such as Cochrane Central Register of Controlled Trials, MEDLINE, Directory of Open Access Journals (DOAJ), and PubMed. Results: The initial electronic database search on PubMed, PMC/MEDLINE, Cochrane Library, and DOAJ resulted in 206 titles. 139 articles were cited as duplicates. After screening the abstracts, 24 relevant titles were selected by two independent reviewers. After prescreening, application of the inclusion and exclusion criteria, and handling of the PICO questions, 8 studies remained. Conclusion: The results of this systematic review and meta-analysis point out that the CTB appliance does not significantly differ from the conventional TB appliance in terms of orthodontic movements. However, patient compliance and satisfaction were greater with CTB appliances.